Gold occurrences in the Kolmozero-Voronya Archean greenstone belt, Kola region: Geological, mineralogical, geochronological and isotope-geochemical characteristics - N. M. Kudryashov; A. A. Kalinin; L. M. Lyalina; P. A. Serov; D. V. Elizarov (Литосфера, 2015)
A multidisciplinary study of the Oleninskoe and Nyalm-1 gold occurrences located in the Kolmozero-Voronya greenstone belt (Kola region) has been carried out. These gold occurrences are interpreted as orogenic and connected with a complex of gabbrodiorite-diorite-granodiorite-quartz porphyry minor intrusions. U-Pb age of zircon from a quartz porphyry dyke in the Oleninskoe occurrence is 2828 ± 8 Ma. An identical age of 2825 ± 7 Ma has been yielded by zircon from a granodiorite porphyry hosting the Nyalm-1 gold mineralization. The gold mineralization was formed in the Neoarchean time after the crystallization of minor intrusions ≈2.83 Ga ago and before the formation of tourmaline-bearing granites and rare-metal pegmatite veins (both dated at ≈2.5 Ga), during hydrothermal alteration of rocks at the retrograde stage of regional metamorphism. Rb-Sr isochron age 2779 ± 72 Ma, obtained for the whole rock samples and apatite from the Nyalm-1 granodiorite porphyry, probably is close to the age of this event. Values of εNd( t ) calculated for granodiorite-porphyries from the Oleninskoe and Nyalm-1 gold occurrences vary from +0.01 to +2.63, suggesting that their parental magma originated from a mantle source and that an addition of crust material was not significant.